Lushio Parfume: Aplikasi Toko Parfum Berbasis Visual Studio. Net Solusi Pengelolaan Stok dan Transaksi yang Efisien - Kafa, Sarah Hidiana; Wulandari, Novi Fitria; Basatha, Rizky (Al-DYAS, 2025)
The problem in this study is that the perfume sales information system that is being used to manage sales data, inventory of goods, and payments is still conventional, namely using a manual bookkeeping system, where operational activities have not used available computer technology or devices. Therefore, the purpose of this study is to design and develop perfume sales applications using visual studio at Galaxy Parfum Shop. The method used in this research is a descriptive qualitative method with data collection techniques in the form of observation, interviews, and literature review. The result of the system created is a perfume sales application that can run well and be implemented. This application is able to provide stock information in real time, manage payments at the cashier, and print notes automatically after payment is made. In conclusion, this application can improve the efficiency of sales management, minimize recording errors, and speed up the transaction process at Toko Galaxy Parfum.